Caring in academia: Exploring the role of values-led practice and research within the doctoral student experience - Michelle Vaughan; Erica Cheva; Reinaldo Ponce; Kimberly Theophile; Márta Vajda (Educational Journal of Living Theories)
In this paper, four American doctoral students and their mentor explore their experiences with Delong’s notion of a ‘culture of inquiry.’ They begin learning experientially to create their living-educational-theories, aiming to improve how they navigate the role of values within their individual practice and research. The doctoral students are experienced professional practitioners in Education with backgrounds in practitioner research. Their mentor, also a professional practitioner in Education, developed her knowledge, understanding, and practice of Living Educational Theory Research over years of mentorship. This account details their activities and research across five sessions held during the first half of the academic year. The intention of publishing their account is to inspire a new generation of doctoral students and mentors to enhance their accountability as professional practitioners, living according to their values by experientially developing their knowledge, understanding, and practice of Living Educational Theory Research together. They include videos, transcripts, and individual reflections to exemplify their concept of ‘caring in academia’ and demonstrate the evolution of their learning as they discover and research their individual, embodied meanings of the ontological value of 'care,' which they each use as an explanatory principle in their explanations of their educational influence on their students' learning.